2013
DOI: 10.1097/rct.0b013e318299f9e7
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Systemic Calcified Atherosclerosis Is Associated With Airflow Limitation and Emphysema

Abstract: The amount of calcification was associated with the extent of emphysema on computed tomography and airflow limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Our study is the first large study to comprehensively investigate the association of COPD with atherosclerotic calcification in different major vessel beds. Previous studies investigating multiple vessel beds in subjects with and without COPD were limited in sample (n = 1154, n = 234 and n = 235) size and did not measure intracranial carotid arteries [10,31,40]. Presence of significant associations in the population-based setting of this study implies a possible stronger link in clinical settings, where COPD is often more severe.…”
Section: Discussionmentioning
confidence: 78%
“…Our study is the first large study to comprehensively investigate the association of COPD with atherosclerotic calcification in different major vessel beds. Previous studies investigating multiple vessel beds in subjects with and without COPD were limited in sample (n = 1154, n = 234 and n = 235) size and did not measure intracranial carotid arteries [10,31,40]. Presence of significant associations in the population-based setting of this study implies a possible stronger link in clinical settings, where COPD is often more severe.…”
Section: Discussionmentioning
confidence: 78%
“…As mentioned in the introduction section, there is limited information on the relationship between COPD severity and the amount of vascular calcifications. Using multiple logistic regression analysis, Chae et al (29) demonstrated age and FEV1/FVC ratio to be independent predictors of the amount of intrathoracic arterial calcifications (Agatston score >1,000) in 206 subjects diagnosed with (mean FEV1%=53.5) or at risk of COPD. Although the proportional distribution of GOLD stages in this cohort is not reported, the findings of Chae et al (29) are in conformity with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Using multiple logistic regression analysis, Chae et al (29) demonstrated age and FEV1/FVC ratio to be independent predictors of the amount of intrathoracic arterial calcifications (Agatston score >1,000) in 206 subjects diagnosed with (mean FEV1%=53.5) or at risk of COPD. Although the proportional distribution of GOLD stages in this cohort is not reported, the findings of Chae et al (29) are in conformity with our results. By analogy to our study, other risk factors such as smoking history, BMI or diffusing capacity for carbon monoxide (DLCO) were not predictive of thoracic arterial calcifications in their multivariable regression model.…”
Section: Discussionmentioning
confidence: 99%
“…The Mesa study also found that FEV 1 was associated with the extent of distal aortic calcification (0.76; 95%CI 0.60–0.97, p =0.02) but not proximal aortic calcification (21). A study by Chae et al found that the amount of vascular calcification was associated with the extent of emphysema on computed tomography and airflow limitation (22). This is in contrast with a recent study from China on elderly smokers with airflow limitation that found no evidence that the association of pulmonary function with CIMT varied by smoking status (23).…”
Section: Discussionmentioning
confidence: 99%